Lectin receptor kinase OsLecRK‐S.7 is required for pollen development and male fertility. Issue 8 (6th March 2020) - Peng, Xiaoqun; Wang, Menglong; Li, Yiqi; Yan, Wei; Chang, Zhenyi; Chen, Zhufeng; Xu, Chunjue; Yang, Chengwei; Deng, Xing Wang; Wu, Jianxin; Tang, Xiaoyan
Abstract: Pollen grains are covered by exine that protects the pollen from stress and facilitates pollination. Here we isolated a male sterile mutant s13283 in rice exhibiting aborted pollen with abnormal exine and defective aperture. The mutant gene encodes a novel plasma membrane‐localized legume‐lectin receptor kinase that we named OsLecRK‐S.7. OsLecRK‐S.7 was expressed at different levels in all tested tissues and throughout anther development. In vitro kinase assay showed OsLecRK‐S.7 capable of autophosporylation. Mutation in s13283 (E560K) and mutation of the conserved ATP binding site (K418E) both knocked out the kinase activity. Mass spectrometry showed Thr376, Ser378, Thr386, Thr403, and Thr657 to be the autophosphorylation sites. Mutation of individual autophosphorylation site affected the in vitro kinase activity to different degrees, but did not abolish the gene function in fertility complementation. oslecrk‐s.7 mutant plant overexpressing OsLecRK‐S.7 recovered male fertility but showed severe growth retardation with reduced number of tillers, and these phenotypes were abolished by E560K or K418E mutation. The results indicated that OsLecRK‐S.7 was a key regulator of pollen development. Abstract : By isolating a recessive mutant gene responsible for a complete male sterile phenotype, we identified the first legume‐lectin receptor kinase in rice, OsLecRK‐S.7, with a function in regulating pollen exine assembly and aperture development. OsLecRK‐S.7 required the kinase activity for its gene function.